Subsurface structure of the offshore Trincomalee, NE of Sri Lanka - Gamage, S. S. N; Silva, K. C. C; Weerasinghe, D. A. (J.Ind. Geophys. Union, 2019)
Lanka basin of Sri Lanka, is an ultra-deep-water basin, which is now in focus due to economic importance, thus needed further exploration. This region consists of a prominent northeast –southwest trending gravity anomaly in the offshore Trincomalee region, which is known as a seismically virgin area. In this study, an attempt was made to generate a subsurface model using the freely available satellite and ship-borne gravity and ship track bathymetry data. An iterative algorithm was developed to calculate the gravity anomaly, caused by a two dimensional polygonal body having a density contrast with the surrounding, constrained further by available seismic data. The gravity anomaly caused by the upper mantle was obtained by arithmetic operations of the calculated gravity anomalies and the satellite derived free air gravity anomaly. Conventional trial and error method was finally employed to determine the structure of upper mantle that indicates the depth of Mohorovićič discontinuity. The lowest thickness of the oceanic crust in the basin is 2 km and the average sedimentary thickness is about 6 to 8 km. The Mohorovićič discontinuity was found to be around 12-14 km along the chosen profile. The results are of significance, as they can be used to interpret the evolution of the basin and depict the interested regional areas for further seismic surveys and oil and gas explorations.
Keywords: Density contrast, Gravity studies, Lanka basin, Mohorovičić discontinuity, Upper mantle, Seismic velocity.